Evaluation of Enamel Surface Roughness after Various Finishing Techniques for Debonding of Orthodontic Brackets - Emire Aybüke Erdur; Mehmet Akın; Leyla Cime; Zehra İleri (Galenos Yayinevi, 2016)
Objective:The aim of this study was to evaluate the surface roughness of enamel after debonding with various types of burs.Methods:The buccal surfaces of 20 mandibular incisors for each group of bur were subjected to profilometer analysis, and three parameters of surface irregularity were recorded. After bracket debonding, adhesive remnants were removed by tungsten carbide burs in low-speed, high-speed, and stainbuster settings. The samples were evaluated at pre-treatment (on sound enamel) (T1) and post-treatment (T2) by a profilometer. The specimens were measured twice, and the mean values were recorded.Results:The results were analyzed in intra-group comparisons with paired t-tests and in inter-group comparisons with one-way ANOVA and Tukey's HSD test. All resin removal techniques significantly increased enamel surface roughness (p<0.05). According to one-way ANOVA, there were significant differences in the effect of enamel surface roughness between all methods (p<0.05). The high-speed bur caused the maximum roughness values and the stainbuster bur caused the minimum roughness values in all the parameters (Ra, Rz, and Rq).Conclusion:The three types of burs used for finishing methods revealed significant differences in the enamel surface after debonding. However, the stainbuster bur created smoother surfaces than the other applied methods.